Lombo tipo canadense elaborado com diferentes teores de carne PSE e cloreto de sódio - Silva, Gabriela de Barros (2016)
Given PSE meat’s high incidence, the need to reduce sodium in food processed products and the sodium chloride’s (salt) assistance to correct eventual defects caused by PSE meat, this research aimed to evaluate cured smoked pork loin formulated with several PSE meat and salt contents in order to establish the highest PSE meat content and the lowest salt content capable of preserving the product’s characteristics. We used a 2x2 Central Composite Design (CCD). We analyzed chemical composition, sodium content, weight losses, pH, TBARS index, water activity (Aw), objective color (L*, a*, b*, C* and h*), texture profile analysis, sliceability and optimal salt sensory evaluation of the products through response surface methodology, whereas sensory acceptance was analyzed through internal preference map (IPM). The response surface model was not significant (P > 0,005) for cooking loss, syneresis, freezing loss, L*, a*, b*, cohesiveness and flexibility, pointing that PSE meat and salt contents do not affect those variables. Protein content, TBARS index, h* and C* were adjusted, but presented low determination coefficients (R 2 ). Chemical composition and sodium content followed the behavior predicted from the raw material composition. The Aw was influenced only by salt content, being lower as higher amount of salt were used. The pH and heating loss were more affected by PSE meat content, wherein pH was lower and heating loss was higher when higher PSE meat was used; both parameters were lower as the salt content was higher. The remaining analyses were influenced mainly by salt content: expressible moisture, hardness, chewiness, adhesiveness and sliceability were higher when salt content was higher and PSE meat content was lower. The sensory test pointed that optimal salt addition was approximately 0,5% for this specific formulation. IPMs pointed the formulations containing 100% PSE meat 1% salt, and 50% PSE meat 0% salt as the least accepted by consumers. Salt content is essential for the product’s quality maintenance when PSE meat is used. When PSE meat was used the formulation should be added at least 1% of salt. However more tests are required to determine maximum PSE meat content which does not affect cured-smoked-pork-loin acceptance.